The Role of Integrated Reporting in Reducing Information Asymmetry: Analytical Research of A sample of Iraqi Banks listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2021)
Allowing Iraqi companies to use multiple systems and policies leads to varying levels of disclosure and no high symmetry between report preparers and users, and that the adoption of integrated reporting can reduce information asymmetry. The theoretical side addressed the concepts of these variables, and in the practical side the binary variable (0, 1) was used. To compensate for the value of the independent variable (integrated reporting) based on the Central Bank of Iraq’s classification of banks according to the (CAMLES) index, and the dependent variable (information asymmetry) was measured through two measures (price difference, unusual return), the research community was represented by (5) Banks out of the total of banks listed in the Iraqi market (43) banks for (5) years (2015-2019) and was based on the hypothesis that there is a relationship between integrated reporting and information asymmetry and reached several results, the most important of which was the presence of information asymmetry in the research sample banks, no There is an effect of adopting integrated reporting on reducing asymmetry.Keywords: Integrated Reporting, Information Asymmetry, Spread, Abnormal Return.